The relationships between vertical variations of shallow gas and pore water geochemical characteristics in boreholes from the inner shelf of the East China Sea - Li, Xue; Duan, Xiaoyong; He, Xingliang; Xie, Yongqing; Yang, Lei; Yin, Ping; Cao, Ke; Chen, Bin; Gao, Fei; Li, Feng (Frontiers in Marine Science, 2024)
Shallow gas was widely recognized in the coastal region, especially in the estuarine delta areas with high organic matter (OM) burial flux. In this study, the vertical variations of shallow gas and the related geochemical indicators from two boreholes in the coastal region of the East China Sea (ECS) were investigated. Two gas-bearing layers were identified in the sediments from the Holocene and late Pleistocene series. Both boreholes exhibit a “typical” and an “inverse” Sulfate Methane Transition Zone (SMTZ). The “typical” SMTZs (SMTZ1 and SMTZ3) were in the upper part of the gas-bearing layers, where sulfate levels decrease and methane levels increase with depth. Conversely, the “inverse” SMTZs (SMTZ2 and SMTZ4) were in the lower part of the gas-bearing layers, exhibiting an increase in sulfate levels and a decrease in methane levels with depth, a phenomenon rarely documented in previous research. The downward variations of pore water geochemical characteristics indicates that these ions were related to Anaerobic Oxidation of Methane (AOM) processes. The increase in Ca2+ and Ba2+ concentrations and the gradual decrease in sulfate at the SMTZ reflect a series of biogeochemical processes resulting from the dissolution of carbonate and other minerals by AOM. The research indicates that sulfate in AOM may originate from multiple sources. Through analyzing the vertical distribution of shallow gas and the geochemical properties of pore water, this study elucidates the shallow gas formation mechanism and the features of the SMTZ, laying the groundwork for further investigations.